Zone‐based tariff design in public transportation networks. Issue 4 (13th February 2017) - Otto, Benjamin; Boysen, Nils
Abstract : Tariff design is among the most elementary decision problems to be solved in every public transportation network. This article focuses on alternative zone‐based tariffs, which vary in the way zones are cut (ring structure vs. connected zones) and fares are calculated (counting zones, cumulative pricing, and maximum pricing), and compares their ability to exploit the customers' willingness to pay. For this purpose, we formulate six versions of the tariff design problem, investigate their computational complexity, and develop suited mixed‐integer models. Our comprehensive computational study reveals that tariffs based on cumulative pricing outperform traditional distance‐based tariffs and are best suited to exploit the customers' willingness to pay. © 2017 Wiley Periodicals, Inc. NETWORKS, Vol. 69(4), 349–366 2017